Penyelesaian Sengketa Terhadap Marhun Yang Masih Berstatus Kredit Ditinjau Menurut Fatwa DSN-MUI Nomor: 25/DSN-MUI/III/2002 - Siregar, Lisa Dewi Rafika Br.; Pulungan, Sahmiar (Faculty of Law, Andalas University, 2023)
This research aims to determine the implementation of pawning on marhun who still have credit status and dispute resolution that occurred in Bangun Sari Village, Silo Laut District, Asahan Regency according to DSN MUI Fatwa number: 25/DSN-MUI/III/2002. This type of research method uses qualitative methods with a field approach (field research). The data sources in this research use two data sources, namely, primary data obtained through interviews, observations of the problem objects raised and secondary data to complement primary data obtained from books, articles, written documents, journals and other related secondary data. with the problems in this research. Meanwhile, the data collection techniques used were interviews, observation and existing literature. The location of this research is in Bangun Sari Village, Silo Laut District, Asahan Regency. The problem of this research is through DSN-MUI Fatwa Number: 25/DSN-MUI/III/2002 concerning Rahn, namely that marhun cannot be used by murtahin unless the murtahin has permission. However, looking at cases in the field, Murtahin is still taking advantage of the marhun by selling it to other parties without Rahin's permission. If the maturity date has passed, Murtahin must warn Rahin to immediately pay off his debt. However, in this case the murtahin did not remind the rahin when the debt was due. If Rahin cannot pay off his debt, Marhun will be forced to sell/execute at auction in accordance with sharia. The results of the research show that the implementation of pawning and dispute resolution for marhun with credit status in terms of the DSN MUI Fatwa in Silo Laut village, Silo Laut District, Asahan Regency is invalid because it does not comply with the provisions contained in the DSN-MUI Fatwa. Meanwhile, according to Islamic law, the implementation of pawning that occurred in Bangun Sari village, Silo Laut subdistrict, Asahan district, was not in accordance with the pillars and conditions of pawning.